HUBUNGAN POLA HIDUP WANITA LANSIA DIMASA MUDA DENGAN DIAGNOSA PENYAKIT DEGENERATIF WANITA LANSIA - Gustina, Irwanti; Dita, Putri Sarah (Universitas Muhammadiyah Tangerang, 2023)
The proportion of the elderly population in Indonesia has both positive and negative impacts. positive if the elderly population is in a healthy, active and productive condition. The elderly become a burden if they have declining health problems such as degenerative diseases. In this study, the authors looked for a relationship between the lifestyle of the elderly at a young age with degenerative diagnoses suffered by the elderly. The sample in this study was the elderly who currently have degenerative diseases. This research design is cross sectional, data collection techniques through questionnaires / questionnaires. From the research results, it was found that there was a significant relationship between degenerative diseases in the elderly with diet, physical activity of the elderly, rest patterns, and health care support for the elderly. Meanwhile, smoking habit with p-value = 0.283 means that statistically there is no relationship between smoking habits and degenerative diseases, this is because the proportion of elderly women who smoke and have degenerative diseases is less. The conclusion of this study is the productivity of the elderly in youth and lifestyle will have an influence on the health of the elderly in old age.